Harmonizing Heritage and Innovation: Leveraging Ethiopia’s Cultural and Religious Values with Science and Technology for Peace and Sustainable Development - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2024)
Ethiopia, a nation with a rich cultural and religious heritage, faces significant challenges in achieving peace and sustainable development amidst ethnic tensions, resource scarcity, and rapid modernization. This study explores the potential of integrating Ethiopia’s cultural and religious values with science and technology to foster peace and development. The research employs a mixed-methods approach, including interviews, focus group discussions (FGDs), surveys, and document analysis, to gather data from the Amhara, Oromia, and Southern Nations, Nationalities, and Peoples' Region (SNNPR). Findings reveal that traditional systems like the Gadaa and Shimgilina are highly effective in promoting peace but are often undermined by political interference and marginalization. Participants expressed openness to integrating science and technology with cultural values, particularly in agriculture, healthcare, and education, but emphasized the need for culturally sensitive approaches. Challenges such as the digital divide, generational gaps, and concerns about cultural erosion were identified. The study concludes that leveraging Ethiopia’s cultural and religious institutions, combined with innovative technologies, offers a unique pathway to peace and development. Recommendations include empowering traditional leaders, bridging the digital divide, and fostering youth engagement through education and digital platforms. Policymakers are urged to adopt inclusive and culturally sensitive strategies that respect Ethiopia’s heritage while embracing modernization. This study contributes to the broader discourse on sustainable development by highlighting the importance of integrating traditional knowledge with modern innovations in conflict-affected regions.